2017
DOI: 10.1002/adfm.201703074
|View full text |Cite|
|
Sign up to set email alerts
|

Exosome as a Vehicle for Delivery of Membrane Protein Therapeutics, PH20, for Enhanced Tumor Penetration and Antitumor Efficacy

Abstract: As biochemical and functional studies of membrane protein remain a challenge, there is growing interest in the application of nanotechnology to solve the difficulties of developing membrane protein therapeutics. Exosome, composed of lipid bilayer enclosed nanosized extracellular vesicles, is a successful platform for providing a native membrane composition. This study reports an enzymatic exosome, which harbors native PH20 hyaluronidase (Exo-PH20), which is able to penetrate deeply into tumor foci via hyaluron… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
94
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(98 citation statements)
references
References 53 publications
3
94
0
1
Order By: Relevance
“…Haney et al (2015) have developed an EVbased antioxidant and catalase delivery system for the treatment of Parkinson's disease. Hong et al (2018) designed a PH20 hyaluronidase delivery nano-system based on EV, which is able to penetrate deeply into tumor foci via hyaluronan degradation, allowing tumor growth inhibition and increased T cell infiltration. There are many other studies that have shown protein or peptide within exosomes provides an intended purpose to targeted therapy.…”
Section: Proteinmentioning
confidence: 99%
“…Haney et al (2015) have developed an EVbased antioxidant and catalase delivery system for the treatment of Parkinson's disease. Hong et al (2018) designed a PH20 hyaluronidase delivery nano-system based on EV, which is able to penetrate deeply into tumor foci via hyaluronan degradation, allowing tumor growth inhibition and increased T cell infiltration. There are many other studies that have shown protein or peptide within exosomes provides an intended purpose to targeted therapy.…”
Section: Proteinmentioning
confidence: 99%
“…Our experiments revealed that the generated exosomes could effectively degrade HA both in vitro and in vivo . Remarkably, PH20 proteins were found to be highly enriched in the lipid raft fraction of these exosomes, and their enzymatic activity was 3-fold higher than that of truncated recombinant proteins [119]. Using the GPI-anchor signal peptide of decay-accelerating factor (DAF), which can be selectively sorted to EVs during reticulocyte maturation, Kooijmans et al further showed that GPI-anchored EGFR nanobodies could effectively bind EGFR-expressing tumour cells under static and flow conditions [99].…”
Section: Therapeutic Applications Of Surface-modified Evsmentioning
confidence: 99%
“…For example, hypoxia-targeting peptides and antibodies could be used to bioengineer the exosomes and enhance their ability to target hypoxic cells in vivo [58,59]. Furthermore, exosomes released from different types of cells, such as cancer cells, immune cells, or stem cells, could be more effective in targeting hypoxic cancer in in vivo [16,60]. Additionally, these in vivo studies could be helpful to understand the role of exosomes as vaccine for cancer immunotherapy [61-63].…”
Section: Discussionmentioning
confidence: 99%